(untitled) (Revista Direito em Debate, 2020)
The objective of the present study is to answer the following research problem: does not the supervision of super indebtedness in the Brazilian legal system have only individual or social consequences? To answer this question, the study assumes that the State has a duty to ensure a dignified life of the citizens subordinated to it. For this, it is necessary to understand the concept of over-indebtedness and its practical consequences, as well as to present arguments for approval of PL 283/2012, which brings greater protection to the indebted and once these new rules are implemented it is possible to reach a medium to combat and prevent the phenomenon of over-indebtedness in society. The appropriate method for approaching the topic will be the meeting of the qualitative approach, through literature review and quantitative approach, through secondary databases, collected mainly from the National Council of Justice. It’s concluded that the lack of protection of super indebtedness stimulates the increase of the problem every year, which has consequences not only to indebted individuals but to society as a whole.